Methods of Sports Genetics: toe and plantar dermatoglyphic analysis (information 3) - Serhiyenko L.P; Lyshevskaya V.H (Kharkov National Pedagogical University, 2010)
The article summarized the data and dermatoglyphic analysis of human toe and plantar prints. It is defined that toe and plantar triradii, papillary ridge patterns, the main plantar lines, the types of dermatoglyphic patterns can be the objects of the dermatoglyphic analysis. The recommendations to use the technology of dermatoglyphic analysis of human toe and plantar prints in sport genetics are given.